Cultural anchoring in cinematic digitalization: Stratified PCA reveals chromatic adaptation regimes in wuxia cinema evolution - Chenyu Liu; Zhe Liu; Yiyang Zhao (PLoS ONE, 2025)
This study decodes cultural chromatic evolution in wuxia cinema using Principal Component Analysis (PCA) of 30 rigorously curated films across three epochs: Celluloid (1960–1979), New Wave (1980–1999), and Digital (2000–2024). Key findings reveal the following: Editing speed (PC1) dominates digital-era films, with cutting rates accelerating by 63% annually (β = 0.63, p < 0.01), fragmenting traditional narrative rhythms; Color stability (PC2) preserves core aesthetics through robust hue-value coordination (r = 0.62, p < 0.001), stabilizing cultural symbolism in wuxia visual motifs; and Saturation adaptation (PC3) activates under high editing intensity to counteract perceptual fragmentation. Crucially, 61% of digital-era films maintained cultural distinctiveness via strategic HSV manipulation, thus demonstrating that cinematic aesthetics actively resists technological homogenization. This reveals a paradigm shift from technological subjugation to chromatic sovereignty in cinematic heritage.